Answer:
[tex]K_{goal}=1.793*10^{-33}[/tex]
Explanation:
N2(g)+O2(g)⇌2NO(g), [tex]K_1 = 4.10*10^{-31}[/tex]
N2(g)+2H2(g)⇌N2H4(g), [tex]K_2 = 7.40*10^{-26}[/tex]
2H2O(g)⇌2H2(g)+O2(g), [tex]K_3 = 1.06*10^{-10}[/tex]
If we add above reaction we will get:
2N2(g)+2H2O(g)⇌2NO(g)+N2H4(g) Eq (1)
Equilibrium constant for Eq (1) is [tex]K_1*K_3*K_3[/tex]
Divide Eq (1) by 2, it will become:
N2(g)+H2O(g)⇌NO(g)+1/2N2H4(g) Eq (2)
Equilibrium constant for Eq (2) is [tex](K_1*K_3*K_3)^{1/2}[/tex]
[tex]Equilibrium constant =K_{goal}= (K_1*K_2*K_3)^{1/2}\\K_{goal}= (4.10*10^{-31} *7.40*10^{-26}*1.06*10^{-10})^{1/2}\\K_{goal}=1.793*10^{-33}[/tex]